Genre and change in the Corpus of History English Texts 1 - Moskowich, Isabel (Nordic Journal of English Studies, 2017)
This paper provides an overview of the Corpus of History English Texts, one of the component parts of the Coruña Corpus of English Scientific Writing (Moskowich and Crespo 2012), looking in particular at the communicative formats that it contains. Among the defining characteristics of the Coruña Corpus are that it is diachronic in nature, and that it can be considered either as a single- or multi-genre corpus, according to the theoretical tenets adopted (Kytö 2010; McEnery and Hardie 2013). The corpus has been designed as a tool for the study of language change in English scientific writing in general, and more specifically in the different scientific disciplines which have been sampled in each subcorpus. All the texts compiled were published between 1700 and 1900, thus offering a thorough view of late Modern English scientific discourse, a period often neglected in English historical studies (De Smet 2005). The analysis of this variety of English is also useful as a means of achieving a clear and detailed description of the origins of English as “the language of science”.